Ethnicity and language change : English in (London)Derry, Northern Ireland - McCafferty, Kevin (Impact, studies in language and society ;, 2001)
Part sociolinguistic, part ethnographic, this book takes up the neglected question of how ethnic division interacts with variation and change in Northern Irish English. It identifies an idealised folk model of harmoniouscommunities, in spite of the social divide and open conflict that have long affected the region; this model affects daily life and sociolinguistic studies alike. A reading of sociolinguistic studies from the region revealsethnolinguistic differentiation. Qualitative analysis of material from (London)Derry shows people often stressing tolerance in their community, while accounts.